An 'open space' approach to the design of residential streets in low-income areas, incorporating the woonerf concept - Swartz, Mark M.(Mark Martin) (Stellenbosch : Stellenbosch University, 2012)
Study project (M. of Town and Regional Planning) -- University of Stellenbosch, 1994.